Cloud Computing Adoption in the South African Public Sector - Bonginkosi Mkhatshwa; Tendani Mawela (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
Scholars have touted a variety of benefits for adopting cloud computing solutions in the public sector. However, the  adoption of cloud computing has been low in the South African (SA) government context. This study investigates the factors influencing cloud computing adoption within the SA public sector. The study adopted a case study approach. The research was informed by the Technological Organisational Environmental (TOE) and the Diffusion of Innovation (DOI) theoretical frameworks to understand the trajectory of cloud computing adoption. Primary data was collected using a questionnaire and semi-structured interviews with respondents from government departments. Additionally, secondary data from government Information Technology (IT) policies and strategic documents was analysed. The results highlighted that the enablers that are critical for cloud adoption include cloud computing policy, skills, IT infrastructure and financial support. The barriers that are hindering cloud adoption are related to security risks, network connection, cloud computing policy, costs and budget availability, among others. The identified benefits that may be realised through cloud adoption include enhanced service improvement, cost savings, high system availability, green IT, centralised and shared services and accessibility. The study proposes several guiding principles for cloud computing adoption in the public sector.